A systematic review and meta‐analysis comparing adverse events and functional outcomes of different pouch designs after restorative proctocolectomy. (19th April 2018) - Simillis, C.; Afxentiou, T.; Pellino, G.; Kontovounisios, C.; Rasheed, S.; Faiz, O.; Tekkis, P. P.
Abstract: Aim: There is no consensus as to which ileoanal pouch design provides better outcomes after restorative proctocolectomy. This study compares different pouch designs. Method: A systematic review of the literature was performed. A random effects meta‐analytical model was used to compare adverse events and functional outcome. Results: Thirty comparative studies comparing J, W, S and K pouch designs were included. No significant differences were identified between the different pouch designs with regard to anastomotic dehiscence, anastomotic stricture, pelvic sepsis, wound infection, pouch fistula, pouch ischaemia, perioperative haemorrhage, small bowel obstruction, pouchitis and sexual dysfunction. The W and K designs resulted in fewer cases of pouch failure compared with the J and S designs. J pouch construction resulted in a smaller maximum pouch volume compared with W and K pouches. Stool frequency per 24 h and during daytime was higher following a J pouch than W, S or K constructions. The J design resulted in increased faecal urgency and seepage during daytime compared with the K design. The use of protective pads during daytime and night‐time was greater with a J pouch compared to S or K. The use of antidiarrhoeal medication was greater after a J reservoir than a W reservoir. Difficulty in pouch evacuation requiring intubation was higher with an S pouch than with W or J pouches. Conclusion: Despite its ease of construction and comparable complication rates, the J pouch is associated with higher pouch failure rates and worse function. Patient characteristics, technical factors and surgical expertise should be considered when choosing pouch design.